Information System Design for New Student Admission (PPDB) at SDN Sukmajaya Depok - Joko Prihambodo; Laela Kurniawati (CV. Publikasi Indonesia, 2025)
The New Student Admission (PPDB) process plays a crucial role in supporting the smooth running of academic activities at SDN Sukmajaya V Depok. However, the manual implementation of PPDB, from registration to data processing, creates a number of obstacles such as the risk of data loss, time inefficiency, and errors in recording. These conditions encourage the need for technology-based solutions to improve the efficiency and effectiveness of the PPDB process. This research aims to design a web-based PPDB information system to facilitate registration, student data management, and report generation. The research method includes data collection through observation, interviews, and literature review, with a system design approach using the Waterfall model. The research stages include requirements analysis, system design, implementation, and testing. The results showed that the PPDB information system designed was able to meet the needs of schools in the process of admitting new students. The system is equipped with main features such as online registration, automatic data validation, and fast report generation, which can reduce errors and speed up the workflow. With the implementation of this system, it is expected that the PPDB administration process at SDN Sukmajaya V Depok will be more efficient and provide convenience for prospective students and parents.